Persepsi Masyarakat Lokal Terhadap Bali Boozy Kitchen & Bar Sebagai Destinasi Hiburan (Jurnal Destinasi Pariwisata, 2025)
Bali’s nightlife tourism is a significant attraction for both domestic and international visitors, especially in areas such as Kerobokan, Seminyak, and Canggu. Bali Boozy Kitchen & Bar, located in Kerobokan Kelod, has emerged as a popular entertainment destination offering a unique experience through its signature arak-based cocktails and vibrant atmosphere. The venue plays an important role not only as a nightlife attraction but also in contributing to the local economy and social welfare. By analyzing the local community’s perceptions of Bali Boozy Kitchen & Bar, stakeholders can better align nightlife tourism development with community interests and socio-cultural dynamics, thereby fostering a sustainable and harmonious relationship between tourism and the local environment.This study employs a qualitative descriptive method focusing on three components of perception: cognitive, affective, and conative. Primary data were gathered through non-participant observation, in-depth interviews with community members and business owners, and documentation analysis. The analytical approach follows the Miles & Huberman model.Findings indicate that local residents generally hold positive perceptions of Bali Boozy Kitchen & Bar. The venue is seen as beneficial for revitalizing local tourism post-pandemic, creating employment opportunities for those affected by COVID-19, and contributing to community welfare through social responsibility initiatives. Moreover, Bali Boozy Kitchen & Bar operations are considered orderly and non-disruptive, with residents appreciating its role in boosting the local economy. It is recommended that future operational improvements address visitor congestion and public facility needs to enhance the overall experience and maintain positive community relations.
Keywords: Community Perception; Nightlife Tourism; Local Economy; Social Responsibility